Work in rehabilitation of persons with disabilities in Poland: formal and legal conditions and reality pragmatics - Szyszka, Michał (Східноєвропейський національний університет імені Лесі Українки, 2016)
In the article the materials of the Act on vocational and social rehabilitation and employment of persons with disabilities are presented by the author. An attention is paid to the definition of persons with disabilities and three degrees of disability (minor, moderate or severe). The author describes the situation of persons with disabilities in Poland, the centers for the disabled that were isolated from institutional and social life. New approach to the “work” in the context of rehabilitation to the persons with disabilities is presented in the article. Work is an important form of social rehabilitation as it introduces the disabled to the environment of healthy persons, integrates and socializes them with the society. A model of the social-vocational rehabilitation is analyzed in the given article. У статті представлені матеріали Акту з професійної та соціальної реабілітації та працевлаштування осіб з обмеженими можливостями. Представлено визначення осіб з обмеженими можливостями та три степені осіб з обмеженими можливостями. Автор описує ситуацію (положення) та центри для осіб з обмеженими можливостями у Польщі, які ізольовані від інституційного та соціального життя. У статті представлено новий підхід до працевлаштування осіб з обмеженими можливостями. Праця є важливою формою реабілітації осіб з обмеженими можливостями, оскільки вона вводить неповносправних в оточення здорових людей, інтегрує й соціалізує їх з суспільством. Модель соціально-професійної реабілітації описано у статті.
Keywords: vocational and social rehabilitation; persons with disabilities; centers for the disabled; social life; sheltered workshops; model of the social-vocational rehabilitation; therapy workshops; practical skills; професійна й соціальна реабілітація; люди з обмеженими можливостями; центри для неповносправних; соціальне життя; криті майстерні; модель соціально-професійної реабілітації; терапевтичні майстерні; практичні уміння